Hemoglobin A1c trajectories in the first 18 months after diabetes diagnosis in the SWEET diabetes registry. Issue 2 (21st December 2021) - Prahalad, Priya; Schwandt, Anke; Besançon, Stéphane; Mohan, Meena; Obermannova, Barbora; Kershaw, Melanie; Bonfanti, Riccardo; Lyckå, Auste Pundziute; Hanas, Ragnar; Casteels, Kristina
Abstract: Aim: A majority of youth with type 1 diabetes do not meet recommended hemoglobin A1c (HbA1c) targets. The SWEET diabetes registry is a multi‐national registry of youth with diabetes. We used data from this registry to identify characteristics associated with glycemic control. Methods: Patients in the SWEET diabetes registry with at least one HbA1c value within 10 days of diagnosis and three follow up measurements in the first 18 months of diagnosis were included (~10% of the SWEET diabetes registry). Locally weighted scatterplot smoothing was used to generate curves of HbA1c. Wilcoxon, Kruskal–Wallis, or χ 2‐tests were used to calculate differences between groups. Results: The mean HbA1c of youth in the SWEET diabetes registry is highest at diagnosis and lowest between months 4 and 5 post‐diabetes diagnosis. HbA1c continues to increase steadily through the first 18 months of diagnosis. There are no differences in HbA1c trajectories based on sex or use of diabetes technology. Youth in North America/Australia/New Zealand had the highest HbA1c throughout the first 18 months of diagnosis. The trajectory of youth from countries with nationalized health insurance was lower than those countries without nationalized health insurance. Youth from countries with the highest gross domestic product (GDP) had the highest HbA1c throughout the first 18 months of diagnosis. Conclusions: In this subset of patients, the trajectory of youth from countries with nationalized health insurance was lower than those countries without nationalized health insurance. High GDP and high use of technology did not seem to protect from a higher trajectory.